ANALISIS VITAMIN B1, VITAMIN B6 DAN VITAMIN E PADA DAGING TOPBLADE SAPI BERBEDA RAS (LOKAL, IMPOR) DAN KERBAU - Mellova Amir (SAINSTECH FARMA, 2012)
A study were conducted to analize the vitamins B1, B6 and vitamin E concentrations of top-blade steak from Indonesian local beef, swamp buffalo and imported wagyu beef. Animals were slaughtered at ± 2 year old, top-blade were removed, aged at 10C for seven days, then stored at-800C, thawed to 50C before analyzed. Vitamins B1, B6, and vitamin E content from different breeding meat and buffalo (P<0.05) were significantly different. The content of vitamins B1, B6 and vitamin E local cattle Indonesia is not different from imported beef, and from buffalo meat even contain the highest vitamin E